2015
DOI: 10.5935/abc.20150058
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ACUITY and CRUSADE Scores in Predicting Major Bleeding during Acute Coronary Syndrome

Abstract: BackgroundThe ACUITY and CRUSADE scores are validated models for prediction of major bleeding events in acute coronary syndrome (ACS). However, the comparative performances of these scores are not known.ObjectiveTo compare the accuracy of ACUITY and CRUSADE in predicting major bleeding events during ACS.MethodsThis study included 519 patients consecutively admitted for unstable angina, non-ST-elevation or ST-elevation myocardial infarction. The scores were calculated based on admission data. We considered majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The proportion decreases among those with complete elementary education (16.7%), being 18.2% among those with complete higher education. 26 However, the ELSA Brazil Study, performed with employees of six Brazilian universities and university-affiliated hospitals with higher schooling, has shown a 35.8% AH prevalence, higher among men. 11 …”
Section: Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion decreases among those with complete elementary education (16.7%), being 18.2% among those with complete higher education. 26 However, the ELSA Brazil Study, performed with employees of six Brazilian universities and university-affiliated hospitals with higher schooling, has shown a 35.8% AH prevalence, higher among men. 11 …”
Section: Conceptmentioning
confidence: 99%
“…A significant association of AH was observed with age, male sex, overweight, central adiposity, sedentary lifestyle during leisure time and work, less than 8 years of schooling, per capita income < 3 minimum wages. 26 …”
Section: Conceptmentioning
confidence: 99%
“…20 In a study by Correia et al, it was reported that the ACUITY scoring system was a better predictor of major bleeding in patients admitted to hospital with ACS compared to the CRUSADE score. 21 These conflicting results suggest that we do not have an ideal scoring system to use on all patients and that new developments are needed in this regard. For this reason, in our study we examined patients with stable coronary artery disease who underwent elective coronary angiography, since there is little data on them and they were often overlooked in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] reported that CRUSADE scores were better able to predict bleeding risk than ACUITY-HORRIZONS scores in 1391 patients with ST-segment elevation myocardial infarction undergoing PCI; however, Correia et al . [ 14 ] found that ACUITY-HORIZONS scores were better than CRUSADE scores in 519 patients with ACS. These discrepancies may be attributable to differences in definition of bleeding and study patients' characteristics.…”
Section: Discussionmentioning
confidence: 99%